Outpatient operative hysteroscopy: evaluation of patient satisfaction and acceptance - Crowley, Clare Margaret; Gill, Noelle; Geisler, Minna (Clinical Journal of Obstetrics and Gynecology, 2022)
Aims: To examine patient satisfaction of an outpatient operative hysteroscopy performed by both doctors and nurse hysteroscopists. Secondly, compare satisfaction, complications, and failure rate of these procedures performed by doctors and nurse hysteroscopists. Methods: In this retrospective study, the charts of 80 women who attended the service over one year were examined. Women were included if either an endometrial polyp or submucosal leiomyoma required removal using an endoscopic morcellator. All women had signed a consent form for the procedure. Results: In total 67/80 (84%) patients were satisfied with the service. Nurse hysteroscopists completed most procedures 59/80 (74%). Satisfaction ratings were not recorded for 13/80 (16%) consultations, completed by doctors. There was no difference in satisfaction and complication rates between doctors and nurse hysteroscopists. A total of five patients required repeat endoscopic morcellation, three completed by doctors and two completed by nurse hysteroscopists. For this group, satisfaction and complication ratings did not change. Conclusion: High patient satisfaction and low complication rates were found. Nurse hysteroscopists performed more procedures, providing a safe and useful service. Few patients required repeat morcellation procedures.